Audit quality, firm value, and audit opinion in Indonesian state-owned enterprises - Lamaya, Fauziyah; Pandin, Maria Yovita R; Ratnawati, Tri (Edelweiss Applied Science and Technology, 2025)
This study aims to investigate the influence of audit quality and sustainability disclosure on audit opinions, with financial risk and firm value serving as mediating variables. The research addresses increasing demands for transparency and accountability in Indonesian state-owned enterprises (SOEs). Using a quantitative approach, data were collected from 20 non-bank SOEs listed on the Indonesia Stock Exchange between 2019 and 2023, resulting in 100 firm-year observations. The analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed mediation model. The findings reveal that audit quality significantly affects audit opinions, both directly and indirectly through firm value. However, sustainability disclosure shows no significant effect on either audit opinions or firm value, and financial risk does not act as a meaningful mediator. The study concludes that audit quality plays a pivotal role in shaping audit opinions, while ESG-related disclosures have not yet been fully considered in public sector audit assessments. These results offer practical implications for policymakers, regulators, and auditors to strengthen audit quality and integrate sustainability information into the audit process.